Victorian labour history : experience, identity and the politics of representation - Host, John, 1946- (Routledge, 1998)
Orthodox historical accounts of popular experience in mid-Victorian Britain suggest certain homogenous and seemingly clear stable social and political orders. Host re-examines the historical debate and challenges conventional interpretations.
Keywords: Labour Party (Great Britain) -- History.; Labour Party (Great Britain); Working class -- Political activity -- Great Britain -- History -- 19th century.; Labor movement -- Great Britain -- History -- 19th century.; Representative government and representation -- Great Britain -- History -- 20th century.; Chartism -- History.; Travailleurs -- Activité politique -- Grande-Bretagne -- Histoire -- 19e siècle.; Mouvement ouvrier -- Grande-Bretagne -- Histoire -- 19e siècle.; Gouvernement représentatif -- Grande-Bretagne -- Histoire -- 20e siècle.; Chartisme -- Histoire.; POLITICAL SCIENCE -- Political Process -- Political Advocacy.; Chartism; Labor movement; Representative government and representation; Working class -- Political activity; Great Britain; 1800-1999; Electronic books.; History